ANALISIS STRUKTUR RETORIKA DAN FITUR LINGUISTIK BAGIAN PENDAHULUAN ARTIKEL JURNAL PENELITIAN BERBAHASA INDONESIA DALAM BIDANG ILMU TEKNOLOGI - Beta Puspa Sari (Universitas Bengkulu, 2017)
The purpose of this study is to describe the rhetorical structure of the introduction section of Indonesian language research journal articles in the field technology and linguistic feature of the introduction of journal articles in Indonesian language studies in the field of technology, using the descriptive research method. This study used a speech in the document text discourse while this research is a source of research journal articles in the field of literature. Rhetorical structure analysis using MMP theory which consists of four moves and 18 steps, while the linguistic features was defined as the use of the type or manner of text associated with active and passive sentences, types of clauses, conjunctions / circuit. The results of the analysis of rhetorical structure articles journal research introduction in the field of literature, such as the use of the move and steps are found or used in the rhetorical structure of article journal research science technology with the result that most are move 1A to equalize background knowledge. While the use of the steps in the move in the field of technology the most widely used in article journal research in the field of humanities, among others: (1) step T1-LC which explains the brief history of the field of research 24%, (2) A second step introduces the research topic 26%, (3 ) step T3-LC states that the important topic of study 32%, (4) Step T4-LA explains the purpose of the study 34%. Furthermore, a new theory is also found in addition to the theory of MMP, among others: (1) step T3-LE stating the results of previous studies. As for linguistic features found in the introduction to article journal research in the field of literature, among others: (1) Active sentence 75%, (2) coordination 27,46%, and (3) subordinate attribute 72,37%.Kata Kunci: Structure, rhetoric, linguistic features, Journal Article Research The purpose of this study is to describe the rhetorical structure of the introduction section of Indonesian language research journal articles in the field technology and linguistic feature of the introduction of journal articles in Indonesian language studies in the field of technology, using the descriptive research method. This study used a speech in the document text discourse while this research is a source of research journal articles in the field of literature. Rhetorical structure analysis using MMP theory which consists of four moves and 18 steps, while the linguistic features was defined as the use of the type or manner of text associated with active and passive sentences, types of clauses, conjunctions / circuit. The results of the analysis of rhetorical structure articles journal research introduction in the field of literature, such as the use of the move and steps are found or used in the rhetorical structure of article journal research science technology with the result that most are move 1A to equalize background knowledge. While the use of the steps in the move in the field of technology the most widely used in article journal research in the field of humanities, among others: (1) step T1-LC which explains the brief history of the field of research 24%, (2) A second step introduces the research topic 26%, (3 ) step T3-LC states that the important topic of study 32%, (4) Step T4-LA explains the purpose of the study 34%. Furthermore, a new theory is also found in addition to the theory of MMP, among others: (1) step T3-LE stating the results of previous studies. As for linguistic features found in the introduction to article journal research in the field of literature, among others: (1) Active sentence 75%, (2) coordination 27,46%, and (3) subordinate attribute 72,37%